Analisis Kebocoran Instalasi Pipa Distribusi Steam pada Boiler untuk Tindakan Pemeliharaan di RSUP. Dr. M. Djamil Padang - Mairizal, Yon; Muknizar, Muknizar; Abu, Risal; Zulkarnain, Zulkarnain; Azman, Azmil (SURYA TEKNIKA, 2023)
Boilers are one of the supporting facilities that play an important role in hospitals. The steam produced by the boiler in the form of saturated steam is used for laundry purposes and to sterilize medical equipment where the temperature must reach/exceed 270 oF. Therefore, the saturated steam produced by the boiler is a source of sterilization used in hospitals today, including RSUP Dr. M. Djamil Padang. The research was carried out to determine the factors that cause leaks and determine appropriate maintenance actions. Based on the research results, it was found that oxidation corrosion and thermal fatigue occurred due to overheating so that the steam distribution pipe cracked/leaked. Maintenance activities: Arranging water access, checking and calibrating temperature and pressure sensors regularly, retubing if the thickness of the distribution pipe is only 71% of the initial design size or painting to protect the pipe in contact with water and air, or the pipe is wrapped in rockwool to prevent metal from coming into contact with water and air